Whose decision? Caesarean section and women with physical disabilities in Northern Vietnam: A qualitative study. (January 2022) - Nguyen, Thi Vinh; King, Julie; Edwards, Niki; Dunne, Michael P.
Abstract: Background: Pregnant women with physical disabilities are more likely to have caesarean sections than are women without disabilities. For some women with disabilities, caesarean birth may not be clinically necessary, as they may lack autonomy in decision-making to a greater extent than is the case for other pregnant women. Objective: To explore the relative influence of health staff, family, friends, and the women themselves on key decisions about childbirth of women with physical disabilities in northern Vietnam. Research design/setting: A qualitative approach using a phenomenological design was employed. Fifty-six in-depth interviews were conducted with women with physical disabilities who had given birth in the previous three years in two northern provinces in Vietnam (Hanoi and Thaibinh). Twenty-nine women participated in a first interview and 27 completed follow-up interviews several months later. Additionally, semi-structured interviews were conducted with 12 maternal healthcare providers. Interviews were transcribed and thematically analysed. Results: Twenty-eight of the 29 participants underwent caesarean sections. Two themes were identified: (1) The women reported that caesarean section was mandated by attending doctors "because of their disability". Consistently, the healthcare providers said caesarean section is essential for women with physical disabilities; and (2) The women said that their parents and peers supported caesarean birth. Very few women indicated that they could influence this decision, even though one-third said their personal preference was for vaginal birth. Conclusions: Many women with physical disabilities are not given the opportunity to exercise informed choices around childbirth options. Women in Vietnam who live with physical disabilities should be empowered to make informed decisions about childbirth. It is recommended that professional guidelines and training are revised to properly engage women with physical disabilities in joint decision-making for the birth of their children.